Aberrant gray matter volume and functional connectivity in Parkinson’s disease with minor hallucination - Zhong, Min; Li, Chenglin; Lu, Hongquan; Xue, Donghui; Wang, Yaxi; Jiang, Yinyin; Zhu, Sha; Gu, Ruxin; Jiang, Xu; Shen, Bo; Zhu, Jun; Zhang, Wenbin; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Minor hallucination (MH) is the most common psychotic symptom in Parkinson’s disease (PD); it can develop into well-structured visual hallucination (VH), suggesting that MH may be a staccato form of well-structured VH. However, it remains unclear whether the pathogenesis is the same. Therefore, the aim of this study was to investigate the altered gray matter volume and functional connectivity of MH in PD to further understand the complex mechanisms. Methods: We included sixty-seven PD patients who attended the outpatient clinic of Nanjing Medical University Affiliated Brain Hospital, and recruited 31 healthy controls (HC). Demographic data and clinical characteristics of all subjects were recorded, and cranial structural MRI and resting-state functional MRI data were acquired. Patients were classified into the PD with MH (PD-MH) group and PD without hallucinations or delusions (PD-NH) group. Voxel-based morphometry was used to analyze the differences in gray matter volume (GMV) in the structural pattern. Seed-based functional connectivity (FC) was used to analyze the functional pattern. Gaussian random field correction was used, with voxel level P<0.001 and cluster level P<0.05 representing statistically significant differences. Finally, the correlation between FC values and scores on the clinical characteristics assessment scale was analyzed. Results: In the GMV analysis, compared to the PD-NH group, the PD-MH group had reduced GMV in the medial superior frontal gyrus (SFGmed). In the FC analysis, the FC between the SFGmed and the left middle occipital gyrus and right calcarine sulcus decreased in the PD-MH group compared with the PD-NH group, while the FC between the left middle temporal gyrus increased. Correlation analysis revealed that the FC values of the SFGmed and right calcarine sulcus were correlated with the assessment scores for anxiety and sleep symptoms. The FC values of the SFGmed and left middle occipital gyrus were correlated with assessment scores for rapid eye movement disorder. Conclusions: The structure and function of visual processing areas are altered in MH patients, and the default mode network and executive control network also play an important role in the generation of MH, suggesting that MH and well-structured VH have similar pathophysiological mechanisms.